Food and Drug Legislation in the New Deal - Jackson, Charles O. (Book collections on Project MUSE., 1970)
In June 1938, Franklin D. Roosevelt signed into law a new Food, Drug, and Cosmetic Act, the first major legislation regulating these industries since the 1906 Wiley law. Eliminating many serious and long-standing abuses in production, labeling, and advertising, the 1938 Act was, in the words of David L. Cowen, ""a milestone in federal interest in consumer protection."" Despite its importance to the American public, however, its passage was effected only after a long, complex battle between conflicting interest groups. This volume is a study in depth of that five-year struggle, fully document.